Is the calorie concept a real solution to the obesity epidemic? - Camacho, Salvador; Ruppel, Andreas (Global health action, 2017)
Background: The obesity epidemic has been growing steadily across the whole world, and so far not a single country has been able to reverse it. The cause of obesity is stated by the World Health Organization as an energy imbalance between calories consumed and calories expended. However, growing evidence suggests that the calorie imbalance concept may not be sufficient to manage and reverse the obesity epidemic. Objective: To discuss the use of the calorie imbalance concept and its elements as a tool for weight management as well as its possible negative consequences and implications for public health, with the aim to point toward the need of an updated concept for causes of obesity. This update should guide public health interventions more efficiently to limit obesity by preventing weight gain or promoting weight loss.Methods: This is a literature reviews based on a semi-structured approach to determine the material to be examined.Results: After revisiting general facts about fat generation and accumulation, we propose an updated concept for the causes of obesity including diet composition and hormonal regulation of fat metabolism.Conclusions: We discuss how this updated concept could benefit the overall efficiency of strategies against obesity, and hypothesize how potential resistance to adopting this new view could be lowered.